2012
DOI: 10.1097/nmc.0b013e318244febc
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Survival Skills Training for Type 1 Diabetes

Abstract: Implications for care include age-appropriate information in a variety of formats, minimizing the invasive nature of the treatment, providing opportunities for demonstration/return demonstration of skills, providing positive support and reassurance, and delivering concentrated instruction related to carbohydrate counting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Newly diagnosed children reported the most important information about their cancer diagnosis was knowing what was going to happen to them and understanding the etiology and prognosis (Freeman, O'Dell, & Meola, 2003). This is similar to information requested by children newly diagnosed with diabetes, who want information to understand their disease and treatment (Alderson, Sutcliffe, & Curtis, 2007;Schmidt, Bernaix, Chiappetta, Carroll, & Beland, 2012). Adolescents newly diagnosed with cancer ranked dealing with procedures as the most important topic followed by relationships with friends and getting back to school as the second and third important topics (Decker, Phillips, & Haase, 2004).…”
Section: Picot Questionmentioning
confidence: 74%
See 3 more Smart Citations
“…Newly diagnosed children reported the most important information about their cancer diagnosis was knowing what was going to happen to them and understanding the etiology and prognosis (Freeman, O'Dell, & Meola, 2003). This is similar to information requested by children newly diagnosed with diabetes, who want information to understand their disease and treatment (Alderson, Sutcliffe, & Curtis, 2007;Schmidt, Bernaix, Chiappetta, Carroll, & Beland, 2012). Adolescents newly diagnosed with cancer ranked dealing with procedures as the most important topic followed by relationships with friends and getting back to school as the second and third important topics (Decker, Phillips, & Haase, 2004).…”
Section: Picot Questionmentioning
confidence: 74%
“…However, a study of 20 hemophilia patients found that developmental level, not age, should be factored into the education (Spitzer, 1992). Studies focused on pediatric patients with epilepsy (McNelis et al, 2007; Ridsdale et al, 1999) and diabetes (Schmidt et al, 2012) identified the following factors that influenced the children’s ability to comprehend information: using words they could understand, receiving noncontradictory information, and feeling that HCPs had time to answer questions.…”
Section: Review Of the Evidencementioning
confidence: 99%
See 2 more Smart Citations